I'm not sure how to do this one.
Follow Math Help Forum on Facebook and Google+
Originally Posted by Neverending I'm not sure how to do this one. $\displaystyle x=3\sin(\theta) \implies \sin(\theta)=\frac{x}{3}$ Using the pythagorean theorem we get the unknown side of the triangle as $\displaystyle \sqrt{9-x^2}$ So we get that $\displaystyle \cos(\theta) =\frac{\sqrt{9-x^2}}{3} \implies \sqrt{9-x^2}=3\cos(\theta)$
wow i've never done something like this before. Thanks for showing me the method!
View Tag Cloud